A state-of-the-art review of primary health care in the Philippines : two decades of government initiative - Bautista, Victoria A. (Quezon City, Philippines : National College of Public Administration and Governance, University of the Philippines, 1999)
This is a revised version of an earlier book written on the state-of-the-art of Primary Health Care (PHC) in the Philippines as an initiative of the Philippine government. Some updating and broadening of data base have been incorporated in this second edition, in effect, improving on the original published some three years ago.
Chapter 1 : Introduction -- Chapter 2 : Pre-devolution -- Chapter 3 : PHC under devolution -- Chapter 4 : Other initiatives related to PHC -- Chapter 5 : Conclusions, issues and recommendations .
Includes bibliographical references and index.
Keywords: PRIMARY HEALTH CARE